PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE TWO STAY TWO STRAY (TSTS) UNTUK MENINGKATKATKAN HASIL BELAJAR IPA SISWA KELAS V A SDN 022 JAYAMUKTI DUMAI TIMUR - Ridwan, Muhammad Ridwan; Alpusari, Mahmud Alpusari; ', Munjiatun (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract. This research is Classroom Action Research (CAR), which is done to improve science learning outcomes graders Jayamukti VA SDN 022 East Dumai by applying Cooperative learning model type two stay two stray. This research was conducted in April 2014 with 2 cycles executed. The subjects were 022 students of class VA SDN Jayamukti East Dumai totaling 32 students were used as the data source. Data collection instruments in this thesis is the observation sheet activities of teachers and students as well as student achievement test. Average student learning outcomes before the 67.19 of 32 students who completed only 14 students with classical completeness and 43.75% of students who did not complete 18 students with classical completeness 56.25%. In this study presented improving student learning outcomes, achievement of mastery of learning outcomes as well as increased activity of the teacher and the student. Average student learning outcomes in the first cycle increased by 4.53 points, ie from 67.19 into 71.72. While the average student learning outcomes in second cycle increased by 5.94 points, ie from 71.72 into 77.66. The percentage of completeness student learning outcomes in the first cycle increased by 25%, from 32 students, who completed 22 students with a percentage of 68.75% and an incomplete 10 students with a percentage of 31.25% while the percentage of completeness student learning outcomes second cycle increased by 21 , ie 88% of the 32 students, who completed 29 percent of students with 90.63% and 3 students who did not complete the 9.37% percentage. Percentage of teacher activity in cycle I and II were 75% increased to 80%. The percentage of student activity in the first cycle and the second is a 85% increase to 90%. It can be concluded that the hypothesis can be accepted. Keywords: Cooperative Learning Model Type two stay two stray, Science Learning Outcomes